The Intellectual origins of terrorism in the vision of Imam Ali (as) a study in Nahj Al – Balaghah - qeisar Abad AL Kareem Jassm ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
ABSTRACT :Terrorism is the charge that befalls Muslims from all walks of life and the Arab and Islamic countries and their reputation and status among the peoples of the world , and that is why today we must follow the example of the Imams of Ahl – Al bayt (peace be upon them) inspired by the lessons ,   There for this study came to be inspired by Imam Ali bin Abe Talib (pb) knowing the intellectual origins of terrorism , what methods he used in his   treatment and how he dealt with events and attitudes that terrorized Muslims . The researcher followed the descriptive and analytical approach in this study and accordingly it wasdivided into two main purposes the first researcher was titled the concept of  intellectual assets of terrorism , while the second researcher called the origins of the intellectual development of terrorism , and the list of sources and references .